2010
DOI: 10.3109/03008207.2010.502982
|View full text |Cite
|
Sign up to set email alerts
|

EMILIN-1 regulates the amount of oxytalan fiber formation in periodontal ligaments in vitro

Abstract: The elastic system fibers comprise oxytalan, elaunin, and elastic fibers, differing in their relative microfibril and elastin contents. Among them, human periodontal ligament (PDL) contains only oxytalan fibers (pure microfibrils). Elastin microfibril interface-located protein-1 (EMILIN-1) is localized at the interface between microfibrils and elastin. We hypothesized that EMILIN-1 may contribute to the formation of oxytalan fibers. We used a small interfering RNA (siRNA) for EMILIN-1 in PDL cell culture to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In contrast with the developmental stage, elongated thick oxytalan fibers with both fibrillin-1 and fibrillin-2 expression were observed in human PDL. This observation supports our previous conclusions regarding the necessity of both fibrillin-1 and fibrillin-2 expression to form thick oxytalan fibers in vitro (22,24). Single expression of fibrillin-2 with a nonfiber structure was widely seen in human PDL.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast with the developmental stage, elongated thick oxytalan fibers with both fibrillin-1 and fibrillin-2 expression were observed in human PDL. This observation supports our previous conclusions regarding the necessity of both fibrillin-1 and fibrillin-2 expression to form thick oxytalan fibers in vitro (22,24). Single expression of fibrillin-2 with a nonfiber structure was widely seen in human PDL.…”
Section: Discussionsupporting
confidence: 91%
“…We have investigated whether formation of thick oxytalan fibers is required for secretion of fibrillin-1 and fibrillin-2 with MAGP or emilin deposition using periodontal fibroblasts (19)(20)(21)(22). We demonstrated that fibrillin-1 suppression did not lead to the formation of fibrillin-2-positive thick fibers, whereas fibrillin-2 suppression led to the formation of fibrillin-1-positive thin fibers, but not thick fibers using non-pigmented ciliary epithelial cells, which also compose oxytalan fibers (23,24).…”
mentioning
confidence: 99%
“…Thus, we focused on microfibril‐related genes in the case of elastic fibres. Microfibrils, which are scaffold fibres of elastic fibres, are constructed by assembling fibrillin‐1 with MFAP4 and EMILIN1 . The mRNA expression level of fibrillin‐1 was downregulated, while the expression levels of mRNAs encoding proteins related to microfibril assembly, such as tropoelastin, MFAP4 and EMILIN1, were upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins (5 µg) were subjected to electrophoresis on 4–12% NuPAGE Bis-Tris gel (Invitrogen) for Western blot analysis, as described previously [10]. The primary antibodies used were those against human fibrillin-1 (mouse monoclonal antibody, clone 11C1.3, Thermo Fisher Scientific Anatomical Pathology, Fremont, CA, USA), MAGP-1 (rabbit polyclonal antibody, Abcam, Cambridge, MA, USA) and β-actin (Sigma-Aldrich) at 1:5000 dilution.…”
Section: Methodsmentioning
confidence: 99%